The Central Council for the Care of Cripples : What it is, and what it does
1933-12 1933 1930s 4 pages THE CENTRAL COUNCIL FOR THE CARE OF CRIPPLES. WHAT IT IS, AND WHAT IT DOES. PATRONESS. H.R.H. THE DUCHESS OF YORK. President: DAME AGNES HUNT, D.B.E., R.R.C. Hon. Treasurer. COLONEL BERTRAM ABEL SMITH, D.S.O., M.C. OBJECTS. The Central Council was formed in 1919 to organise a national scheme to deal with the cripple problem as a whole throughout the United Kingdom, and more particularly :— (a) to organise the provision of facilities for the early discovery and the prompt and efficient treatment of children who would otherwise become cripples. (b) to promote schemes for the treatment, education, training, employment and general welfare of all cripples. (c) to assist in the formation of local Associations to carry out these objects. (d) to investigate the causes of crippling and promote and support measures for their elimination. (e) to act as a central co-ordinating body for all organisations working for the benefit of cripples and as a central bureau of information on all matters which concern the welfare of cripples. 292/841.51/2/4